'In the Midst of Three Fires, a French one, an American one, and an Indian one': Imperial-Indigenous Negotiations during the War of 1812 in Eastern British America. (20th August 2021) - Reid, John G.
Abstract : page_15 other This essay argues that the War of 1812 in Eastern British America, despite the near-absence of land-based conflict in this region, marked a turning point in an imperial-Indigenous relationship that differed notably from comparable relationships elsewhere in North America because of the relatively late advent of substantial settler colonization. Diplomacy, which led in 1812 to the conclusion of a series of neutrality agreements in the borderland jurisdiction of New Brunswick, contributed to the forestalling of outright military conflict in the region. But diplomacy of this nature at the same time reached the end of its effective life, as the balance tipped towards a settled environment that eroded the effectiveness of the formerly powerful diplomatic tools of Indigenous-imperial negotiation. 1